Military medics express regret over UK’s past treatment of LGBT+ armed forces personnel - Rimmer, Abi (BMJ (Online), 2023)
The review, conducted by Terence Etherton, examined an official policy that effectively banned from the armed forces anyone who was gay, lesbian, transgender, transitioning because of gender dysphoria, or perceived to be such.1 During the period of the ban, from 1967 to 2000, medics were under an obligation to report any evidence of homosexuality to command. The government’s response to Etherton’s review says that DMS, which provides healthcare services for all armed forces personnel, deeply regrets the past treatment of LGBT+ staff by some members of the military medical community.2 It says that DMS recognises that the historical medical interventions described in the report were inappropriate, unacceptable, and wrong. GP awareness Research carried out in a collaboration between the charity Fighting With Pride and the Northern Hub for Veterans and Military Families Research team at Northumbria University found that veterans who had been subject to the ban felt a sense of fear and shame that often prevented them from getting support.3 The researchers said, “The fear and shame was brought about by traumatic experiences of medical examinations, offensive questioning during interviews and being referred for psychiatric assessment for identifying as LGBT+.